DEVELOPING POLITICAL EDUCATION SKILLS AMONG STUDENTS AS A PEDAGOGICAL NECESSITY - Eshimbetova, Gulzar Turymbetovna (SCIENCE and SOCIETY, 2026)
The article examines one of the most pressing issues of our time – increasing the political literacy of young people, the state of work in this area and the main directions of development of pedagogy.